2018
DOI: 10.1039/c7fo01516j
|View full text |Cite
|
Sign up to set email alerts
|

Can coconut oil and treadmill exercise during the critical period of brain development ameliorate stress-related effects on anxiety-like behavior and episodic-like memory in young rats?

Abstract: CO and exercise during lactation can ameliorate the effects of stress on anxiety-like behavior and episodic-like memory in young rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
2
6
0
7
Order By: Relevance
“…However, none of the chronic effects of C10 reached the study‐wide statistical significance, and further study will be needed to confirm the findings of antidepressant effect. It has been recently reported that chronic treatment with a KD and MCT diet induced decreased anxiety‐ and depression‐like behaviors in rodents 8,9,11,12,27 . Our study suggests that C10 is one of the fatty acids partially contributing to the antidepressant‐like effects.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, none of the chronic effects of C10 reached the study‐wide statistical significance, and further study will be needed to confirm the findings of antidepressant effect. It has been recently reported that chronic treatment with a KD and MCT diet induced decreased anxiety‐ and depression‐like behaviors in rodents 8,9,11,12,27 . Our study suggests that C10 is one of the fatty acids partially contributing to the antidepressant‐like effects.…”
Section: Discussionsupporting
confidence: 57%
“…Acute injection of fatty acids, including one of the medium‐chain fatty acids, lauric acid (dodecanoic acid; C12), is suggested to contribute to a decrease in anxiety‐like behavior 10 . Chronic administration of coconut oil or MCT diet has also been reported to decrease anxiety‐like behaviors in rats 11,12 . These findings suggest that acute and chronic administrations of MCTs have anxiolytic and antidepressant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, coconut oil, which mainly contains LA [7], induces enhanced memory function and reduces the anxiety-like behavior though LA. However, it has lesser ability to produce astrocytic ketone bodies compared to caprylic acid [5,8,42]. Moreover, it has been demonstrated that coconut oil directly activates the neuronal ERK and Akt signaling to prevent amyloid β toxicity [6].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MCFAs not only provide ketone bodies but also protect cortical neurons against amyloid β-induced toxicity [6]. Coconut oil, which contains a high amont of LA [7], prevents stress-induced depressive-and anxiety-like behaviors in rodents [8]. Although the beneficial effect of MCFAs is gradually being recognized, their effect on neuronal functions has not been well-understood.…”
Section: Introductionmentioning
confidence: 99%
“…The combined products were found to be almost twice as effective as the products in isolation. CO and exercise during lactation can ameliorate the effects of stress on anxiety-like behavior and episodic-like memory in young rats through evaluation cognitive test Mini-Mental State Examination for changes (da Silva et al, 2018).…”
Section: Effect Of Coconut In Treatment Of Diabetes and Hypertensionmentioning
confidence: 99%